Unique community structure of viruses in a glacier soil of the Tianshan Mountains, China - Han, Li-Li; Yu, Dan-Ting; Zhang, Li-Mei; Wang, Jun-Tao; He, Ji-Zheng (Journal of soils and sediments, 2017)
Purpose Glaciers of the Tianshan Mountains have been geographically isolated for a long time with little human interference. This study aimed to understand the viral community structures and their ecological functions in a unique glacier soil. Materials and methods The abundances of purified virus particles and bacteria in the glacier soil were examined using epifluorescence microscopy and quantitative PCR of the 16S rRNA gene, respectively. Metagenomic analysis was employed to investigate the taxonomic and functional compositions as well as the phylogenetic relationship of the functional genes of the viruses in the glacier soil. Results and discussion A total of eight double-stranded DNA (dsDNA) virus families were identified in the glacier soil, with Siphoviridae , Podoviridae , and Myoviridae being the more abundant families. The diverse dsDNA viruses and few ssDNA and other types of viruses formed the unique community structure of viruses in the Tianshan Mountains glacier soil. The functional genes identified from the virome mainly belonged to phage-related proteins. The phage terminase of Caudovirales presented high diversity, and its amino acid sequences were different from those in other environments. Conclusions The results showed a unique viral diversity and taxonomic composition in the glacier soil, which suggests the significant ecological role of Caudovirales in this environment.